Politics, Development and Security in Oceania - Hegarty, David (ANU Press, 2013)
The chapters in this volume canvass political change and development across the Pacific Islands from a variety of perspectives, each contributing to the analysis of a region growing in complexity and in confidence. They fall neatly into three sections: Oceania and its Inheritance; Oceania - Current Needs and Challenges; and Oceania and its Wider Setting. The new states of the Pacific have demonstrated considerable resilience, and in many cases, an extraordinary capacity to bounce back from difficulty and to maintain optimism for the future. The continuing professionalisation of public management across the region is building on that tradition. The growth of civil society organisations is also beginning to play a positive role in policy and implementation. Donors are becoming more coherent in their strategies, more attuned to the realities of generating development outcomes in small island states, and are beginning to acknowledge and map progress. This book explores these themes of governance, development and security that signal both continuity and change in the Pacific's pattern of islands.